IMPLIKASI PRINSIP SYARI’AH TERHADAP PENGATURAN ASURANSI DALAM SEKTOR TRANSPORTASI DI INDONESIA - Nugraha, Muhammad Al Haadi; Desril, R (JOURNAL EQUITABLE, 2025)
Sharia insurance emerges as an alternative to address the issues found in conventional insurance practices, which contain elements of gharar (ambiguity), riba (interest), and maisir (gambling). The transportation sector in Indonesia, with its high risks such as accidents and cargo damage, requires insurance protection based on sharia principles. This study aims to analyze the provisions of sharia insurance that conflict with conventional insurance in the transportation sector and the implementation of sharia principles in this sector. The research method used is normative legal research with a descriptive-analytical approach, analyzing applicable regulations and related literature. The findings show that sharia insurance prioritizes justice, transparency, and mutual assistance among participants. The main challenge is the lack of public understanding of this system. Recommendations for the government and insurance companies include strengthening regulations and conducting education to promote sharia insurance in the transportation sector.